Young patients show poor efficacy for immune checkpoint inhibitor combined therapy in metastatic gastrointestinal cancers - Wang, Yingnan; Zhang, Shasha; Zhang, Fengbin; Wang, Lei; Wu, Chensi; Zhang, Xiaoyun; Zhang, Ruixing; Guo, Zhanjun (Frontiers in Oncology, 2023)
Background: The impact of age on the efficacy and safety of immunotherapy still remains controversial. The previous studies simply classified patients into younger and older groups might not reflect the real impact of young age on immunotherapy efficacy. The current study aimed to explore the efficacy and safety of immune checkpoint inhibitors (ICIs) combined therapy in young (aged 18-44 years), middle-aged (aged 45-65 years), and old (aged >65 years) patients with metastatic gastrointestinal cancers (GIC), and further determine the role of immunotherapy in young patients. Methods: Patients with metastatic GIC including esophageal cancer (EC), gastric cancer (GC), hepatocellular cancer (HCC) and biliary tract cancers (BTC), who received ICIs combination therapy were enrolled, divided into young (aged 18-44 years), middle-aged (aged 45-65 years), and old (aged >65 years) groups. The clinical characteristics, the objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and immune-related adverse events (irAEs) were compared among three groups. Results: A total of 254 patients were finally included, with 18, 139, and 97 cases in the young (aged 18-44 years), middle-aged (aged 45-65 years), and old (aged >65 years) groups, respectively. Compared to middle-aged and old patients, young patients owned lower DCR (All P<0.05) and also suffered inferior PFS (P<0.001) and OS (P=0.017). The multivariate analyses showed that young age was an independent prognostic factor for PFS [hazard ratio (HR) 3.474, 95% confidence interval (CI) 1.962-6.150, P<0.001] and OS [HR 2.740, 95% CI 1.348-5.570, P=0.005]. Subsequent safety analyses referring to irAEs demonstrated that no significant differences for distribution frequency among each age group (All P>0.05), whereas patients with irAEs displayed better DCR (P=0.035) and PFS (P=0.037). Conclusion: Younger GIC patients (aged 18-44 years) showed poor efficacy for ICIs combined therapy, and irAEs could be used as a clinical biomarker to predict ICIs efficacy in metastatic GIC patients.